(untitled) (Sociologisk Forskning, 2020)
Worrying about the consequences of climate change. Climate behaviour and the meaning of caring for future generations The aim of the study was to see how care-worry about the consequences of climate change for future generations are experienced and handled by informants in a Swedish context. The term care-worry refer to an assembly of several approaches, such as empathy, care, responsibility, worry, and justice towards other people and coming generations. Care-worry is related to and initiates people’s attitudes and behaviours towards future risks. Empirically, the study is based on thematic interviews conducted in the year 2016 and deals with informants who explicitly expressed worries about climate change for future generations. All 24 informants turned out to be parents. From the material, four ideal types were depicted, which in different ways can illustrate the parents’ care-worry. Different climate behaviours also seem to be linked to these ideal types. The study as a whole shows that parents’ care-worries affect them in various ways to reduce their own climate footprint in the future. Many of them choose a more sustainable lifestyle for the sake of future generations.